THE MEANING OF GENETICS - Adolphs, Svenja; Hamilton, Craig; Nerlich, Brigitte (International Journal of English Studies, 2003)
Research into the public understanding of genetics has greatly expanded lately. At the same time inatters relating to biotechnology have scizcd the public's attention. Corpus linguistics has long asked questions about how meaning is created and changed in the public sphere through language use. However, linking Corpus linguistics to the study of the public understanding of science is something too few have done. To correct this trend, we apply methods from corpus linguistics and cognitive linguistics to study how people talk about genetics. We do so by analysiny the mieaning of words like gene, genes, genetic, genetics, and genetically as found in various spoken and written corpora. Specifically, we examine how they take on certain (e.g. figurative) connotations and modulate in context.